A vaccine targeting mutant IDH1 in newly diagnosed glioma - Platten, Michael; Bunse, Lukas; Wick, Antje; Bunse, Theresa; Le Cornet, Lucian; Harting, Inga; Sahm, Felix; Sanghvi, Khwab; Tan, Chin Leng; Poschke, Isabel; Green, Edward; Justesen, Sune; et al. (Nature, 2021)
Mutated isocitrate dehydrogenase 1 (IDH1) defines a molecularly distinct subtype of diffuse glioma1-3. The most common IDH1 mutation in gliomas affects codon 132 and encodes IDH1(R132H), which harbours a shared clonal neoepitope that is presented on major histocompatibility complex (MHC) class II4,5. An IDH1(R132H)-specific peptide vaccine (IDH1-vac) induces specific therapeutic T helper cell responses that are effective against IDH1(R132H)+ tumours in syngeneic MHC-humanized mice4,6-8. Here we describe a multicentre, single-arm, open-label, first-in-humans phase I trial that we carried out in 33 patients with newly diagnosed World Health Organization grade 3 and 4 IDH1(R132H)+ astrocytomas (Neurooncology Working Group of the German Cancer Society trial 16 (NOA16), ClinicalTrials.gov identifier NCT02454634).
Gesehen am 26.03.2021